Effects of high-intensity interval training using "Tabata protocol" on respiratory parameters, special endurance, and 800-m runners` performance - Megahed, M.; Al-Torbany, M.; Al-Ghool, M.; Tarek, Z. (Journal of Human Sport & Exercise, 2023)
This study aims to investigate the effects of high-intensity interval training using the Tabata protocol on respiratory parameters, special endurance (cardiorespiratory endurance, anaerobic speed endurance, and strength endurance), and 800-m runners` performance. A total of 20 well-trained males in the 800-m running were assigned into two equal groups, the experimental group, and the control group, and all mentioned variables were measured before and after 8 weeks of the intervention. Respiratory parameters were assessed by using a BTL-08 Spirometer device. Cooper`s 12-min running test was used to measure cardiorespiratory endurance. A repeated sprint test (6x30-m) was used to assess anaerobic speed endurance. Tests for strength endurance consisted of repeated squat and sit-ups tests. The main findings indicate that the experimental group showed greater improvement in respiratory parameters, cardiorespiratory endurance, anaerobic speed endurance, strength endurance, and 800-m runners` performance than the control group; where (ES˜ 0.42:0.65, 0.34, 0.31:0.76, 0.48:0.63 and 0.72) (p < .05), respectively. Both groups significantly increased the respiratory parameters, cardiorespiratory endurance, and strength endurance tests from pre- to post-test (p < .05). The experimental group significantly increased the repeated sprint test values from pre to post-test (p = .000, < .05). The control group significantly increased the peak and mean sprinting speed from pre to post-test (p = .039, .005, < .05), while there were no significant differences in the fatigue index (p = .051 > .05). Our results suggest that runners after Tabata protocol interventions can obtain better pulmonary function, endurance, and event time benefits with more efficient performance and time-efficient manner compared with traditional training.